PENGARUH HARGA, PROMOSI, BUKTI FISIK, DAN KUALITAS LAYANAN TERHADAP MINAT BERKUNJUNG KE DYNASTY WATER WORLD GRESIK - VENNY KARTIKA SARI (Jurnal Manajerial, 2018)
This study aims to analyze the effect of price, promotion, physical evidence, and service quality on interest in visiting Dynasty Water World Gresik. The sample of this study consisted of 100 respondents. The independent variables in this study are price, promotion, physical evidence, and service quality, while the dependent variable is the interest in visiting Dynasty Water World Gresik. The data analysis technique used is multiple linear regression with the help of SPSS program. The results showed that the promotion variables, physical evidence, and service quality had a partial effect on the interest in visiting, while the price variable was stated not to have a significant effect on the interest of visiting visiting Dynasty Water World Gresik.